2012
DOI: 10.1007/s10865-012-9413-5
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication among traumatized youth: structural equation modeling of pathways between trauma history, substance misuse, and psychological distress

Abstract: In an effort to self-medicate psychological distress stemming from exposure to traumatic life events, at-risk youth may be likely to seek intoxication via substance use. Concomitantly, self-medication with psychoactive substances is theorized to confer risk of developing future psychiatric and substance use disorders. The present study employed structural equation modeling to examine self-medication among a sample of 723 youth in residential treatment for antisocial behavior via recursive and non-recursive rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 50 publications
1
50
0
Order By: Relevance
“…Research on racial discrimination, for instance, has found that engaging in substance use to cope with racial discrimination moderated the relationship between discrimination and substance use over time (Gerrard et al, 2012). Psychological distress related to a young person’s gender identity may similarly influence substance use as a method of coping (Garland et al, 2013). These relationships could also be explained by the “minority stress” theory, which describes how chronic stress—including discrimination and trauma—experienced by minority groups can lead to negative health outcomes and increased risk behaviors (Hatzenbuehler, 2009; Hatzenbuehler et al, 2008; Meyer, 1995, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Research on racial discrimination, for instance, has found that engaging in substance use to cope with racial discrimination moderated the relationship between discrimination and substance use over time (Gerrard et al, 2012). Psychological distress related to a young person’s gender identity may similarly influence substance use as a method of coping (Garland et al, 2013). These relationships could also be explained by the “minority stress” theory, which describes how chronic stress—including discrimination and trauma—experienced by minority groups can lead to negative health outcomes and increased risk behaviors (Hatzenbuehler, 2009; Hatzenbuehler et al, 2008; Meyer, 1995, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, in reality men and women’s pathways to prison may be very different. Prior research demonstrates that trauma exposure may lead to exacerbated substance use and mental health problems (Garland, Pettus-Davis, & Howard, 2012; Jordan et al, 2002). The fact that women prisoners report more experiences of prior victimization than men prisoners is just one example of why teasing out the differences between men and women prisoners is so critical for the most effective correctional intervention development.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, childhood trauma adversely affects endocrinological functioning and the stress response (Kempke et al, 2015), and the prevalence of childhood trauma is high amongst the homeless (Sundin & Baguley, 2015), and the incarcerated (Singleton, Meltzer, & Gatward, 1997), contributing to people with serious multiple deprivations, including substance use problems, homelessness, mental health problems and prison records (Bramley et al, 2015). Drugs and alcohol can also be used as avoidant coping to escape the intrusive thoughts and feelings of PTSD (Brady & Back, 2012;Garland, Pettus-Davis, & Howard, 2013). Moreover, childhood trauma additionally worsens the progression and outcome of problematic drug use (Heffernan et al, 2000;Lake et al, 2015).…”
Section: Introductionmentioning
confidence: 99%